Quality of life, stress, occupation status of immigrants: predictors of psychological health condition among the gulf return migrants in India - Banerjee, Snigdha (International Journal Of Community Medicine And Public Health, 2022)
Background: The instances of mental health problems are much more frequent among migrants who have faced adversity at the destination as they employed in precarious or insecure jobs. Those who returned as a failure, feeling valueless upon return and lack of suitable job at the place of origin triggered the feeling of distress among the returnees. Therefore, the main objective of this paper was to examine the quality of life, occupational status and its impact on psychological health condition of the gulf return migrants in India. Methods: 330 gulf returnees were interviewed with the help of a structured interview schedule and in-depth interviews were also conducted. Binary logistic regression has been used to determine the significant predictors of self-rated psychological health condition among the return migrants. For this purpose, the self-reporting questionnaire used to understand the mental health status. Results: High prevalence (60%) of mental health distress among the returnees was observed. Factors such as age at the time of return, typology of returnees, feeling sick in the destination country, duration of stay in destination, occupational status after return and reasons for return were found to be significant predictors of mental health distress. Conclusions: The returnees deal with significant mental health distress. Special attention should be paid on this issue. Migrants should access post return counselling related to job market and mental health services in origin.